EFEKTIVITAS KOMUNIKASI PROGRAM PARTISIPASI MASYARAKAT OMBUDSMAN RI PROVINSI RIAU DALAM MENINGKATKAN PENGETAHUAN SAHABAT OMBUDSMAN MENGENAI MALADMINISTRASI - Vania Ramadhani; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In order to assess the effective communication in a public relations program, its main principles are needed, among others; credibility, context, content, clarity, continuity and consistency, channel, and capabilities or capabilities of the audience. One of the agencies implementing the program with the function of public relations is called the community participation program, activities carried out with the community called